2007
DOI: 10.5688/aj710342
|View full text |Cite
|
Sign up to set email alerts
|

An Instructional Seminar for Online Case-Based Discussions

Abstract: Objective. To assess a training seminar developed to prepare pharmacy instructors to facilitate online discussions. Design. A 2-part seminar was developed to train faculty members and teaching assistants to facilitate online case-based discussions. A preseminar survey instrument was distributed to potential attendees and a postseminar survey instrument was given to those who attended the seminar. Assessment. Twenty (91%) instructors completed the preseminar survey instrument. Eleven of these instructors attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…This will result in more accurate and useful design and development of coursework. LeBlanc et al (2007) examined pharmacy instructors to help online discussions. After attending a training seminar, participant's comfort level in their ability to teach online increased.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…This will result in more accurate and useful design and development of coursework. LeBlanc et al (2007) examined pharmacy instructors to help online discussions. After attending a training seminar, participant's comfort level in their ability to teach online increased.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Azara, 2003;Benaya et al, 2010;Domizi, 2013;Negovan and Osiceanu, 2012) and other contemporary disciplines (e.g. Allen et al, 2000;Beaton, 2007;Hrastinski and Jaldemark, 2012;Jaarsma et al, 2009;LeBlanc et al, 2007;Spruijt et al, 2013) have prescribed recommendations for using seminars in their corresponding settings.…”
Section: Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…King et al found that online synchronous problem-based learning in an interprofessional health science course might be beneficial [ 15 ]. A practice session for both faculty and participants to overcome technical issues before starting a module is recommended and the importance of good communication online must be emphasised (since nonverbal communication is limited) [ 15 , 16 ]. Another advantage of online courses is the possibility of a worldwide interaction without the need for travelling [ 16 ].…”
Section: Introductionmentioning
confidence: 99%